Analisis Dampak Pandemi Covid-19 terhadap Perubahan Fokus Corporate Social Responsibility (CSR) pada Uniqlo Co., Ltd - Marwa Mutiara Sati; Charoline Cheisviyanny (Jurnal Eksplorasi Akuntansi, 2023)
This study aims to analyze: 1) The level and quality of Corporate Social Responsibility (CSR) disclosure before and during the COVID-19 pandemic of Uniqlo Co., Ltd for the year 2016-2021 based on the GRI 2021 Standard, 2) Differences in focus changes of CSR before and during the COVID-19 pandemic at Uniqlo Co., Ltd. This research is a qualitative research with analysis content method using Sustainability report of Uniqlo Co., Ltd for the year 2016-2021. The object in this study is Uniqlo Co., Ltd. The type of data were documentary data with secondary data sources and the analysis method were content analysis. The result show that: 1) The level and quality of disclosure of Uniqlo’s CSR during the COVID-19 pandemic decreased compared to before the COVID-19 pandemic, 2) There is a change in the focus of Uniqlo's corporate social responsibility during the COVID-19 pandemic. Uniqlo shifted the focus of CSR from environmental (300) to significant indirect economic impacts (203-2) and prevention and mitigation of occupational health and safety impacts directly linked by business relationships (403-7).